Substantiation of claims of diaphragm wall of BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding substantiation of claims of diaphragm wall having reference number BUCG-ABC JV-JAA-019 dated 28th January 2018, BUCG-ABC JV/BRACU/03/18 dated 25th February 2018 and BUCG-ABC-JV/BRACU/15/18 dated 4th April 2018 of BRAC University new campus project.